Successful second hematopoietic cell transplantation in severe congenital neutropenia. (26th October 2017) - Hashem, H.; Abu‐Arja, R.; Auletta, J. J.; Rangarajan, H. G.; Varga, E.; Rose, M. J.; Bajwa, R. P. S.
Abstract: Allogeneic HCT is curative for SCN; however, a standard conditioning regimen or intensity has not been established. We describe a patient with SCN associated with c.1A>G (M1V) mutation in ELANE gene resulting in refractoriness to G‐CSF, who received reduced‐intensity HCT and developed secondary graft failure requiring a second myeloablative HCT. This case suggests that M1V mutation confers a poor G‐CSF response and HCT using the best available donor is beneficial.